Introduction of pathogenic mutations into the mouse Psen1 gene by Base Editor and Target-AID - Hiroki Sasaguri (Nature Portfolio, 2018)
CRISPR-guided cytidine deaminases, including BE3 (Base Editor 3) and Target-AID (activation-induced cytidine deaminase), can covert C:G base pairs to T:A at target site. Here, the authors generate missense mutations of mouse Psen1 gene and find BE3 has higher editing efficiency than Target-AID.